Faktor-Faktor Berat Badan Lahir Rendah (BBLR) di Puskesmas Bawangan Ploso Kabupaten Jombang: (Analisis Data Sekunder Kohort Ibu Hamil dan Bayi Tahun 2020) - Halimatus Sa’adah; Siti Nurrochmah; Ema Novita Deniati (Lembaga Pengembangan Kinerja Dosen, 2024)
Cases of death in infants can be caused by several factors, one of which is Low Birth Weight (LBW). Babies born with low birth weight have a higher risk of experiencing delays in growth and development during childhood, and can even cause death compared to babies born with normal weight. Factors that affect LBW include: baby's length, mother's weight gain, mother's age, LILA, parity, birth spacing, nutritional anemia, and ANC. The purpose of this research is to find out the factors associated with LBW at the Bawangan Ploso Health Center, Jombang Regency, East Java Province in 2020. This research is a quantitative study with a cross sectional approach. The population in this study were all births recorded in the infant cohort data and data on pregnant and giving birth in the Bawangan Ploso Health Center, Jombang Regency for the period January 2020 to December 2020. The number of babies born in that period was 604 babies. Sampling used purposive sampling with a total sample of 100 respondents determined by inclusion and exclusion criteria. The results showed that the baby's length was pertinent to LBW (p = 0,000 < 0,05), maternal weight gain was pertinent to LBW (p = 0,000 < 0,05), maternal age was pertinent to LBW (p = 0,002), LILA was pertinent to LBW (p = 0,000 < 0,05), parity was not pertinent to LBW (p = 0,096 > 0,05), birth spacing was pertinent to LBW (p = 0,000 < 0,05), nutritional anemia was pertinent to LBW (p = 0,000 < 0,05), and ANC was not pertinent to LBW (p = 0,243 > 0,05). Based on the multivariate test, the weight gain of pregnant women is the dominant factor that influences the incidence of LBW.